MODERN MEANS OF ELECTRONIC PROCESSING OF SOCIO-ECONOMIC INFORMATION - M. Bogdanova; L. Parshintseva (Вестник университета)
The article analyzes most popular software packages for statistical analysis of economic information, identified their merits and demerits, developed recommendations for choice of statistical packages